SPECIFIC ASPECTS OF USING MODERN MARKETING TOOLS IN HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
The article examines the role of modern marketing tools amid growing competition in the educational services market. It focuses on higher education institutionsʼ management, reputation building, graduate demand forecasting, and competitiveness enhancement. Using the "7P" model, key elements of higher education marketing are analyzed. The practical importance of relationship marketing in achieving social impact is highlighted. Foreign experiences are reviewed, and context - specific recommendations for Uzbekis tan are proposed. The study emphasizes the need for a systematic marketing approach in higher education administration.
Keywords: education marketing; competitiveness; higher education; relationship marketing; demand forecasting; "7P" model. № 1 375